PERAN GURU SEBAGAI INOVATOR DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI ERA DIGITAL - FITRIA ANGGRAINI, DEWI (Fakultas Agama Islam Universitas Kutai Kartanegara Tenggarong, 2025)
This research aims to describe the role of teachers as innovators in digital learning in the technology era. Through a literature review, it was found that the integration of ICT such as Zoom, Edmodo, and Google Classroom can enhance student motivation, digital literacy, and collaboration. Active learning models such as flipped classroom and discovery learning also encourage student engagement in a critical and creative manner. Although faced with infrastructure challenges and teacher competencies, continuous training and support from educational institutions are essential. These results emphasize the important role of teachers as key drivers in technology-based educational transformation.